2005
DOI: 10.1634/stemcells.2004-0236
|View full text |Cite
|
Sign up to set email alerts
|

Biological Activities Encoded by the Murine Mesenchymal Stem Cell Transcriptome Provide a Basis for Their Developmental Potential and Broad Therapeutic Efficacy

Abstract: We used serial analysis of gene expression to catalog the transcriptome of murine mesenchymal stem cells (MSCs) enriched from bone marrow by immunodepletion. Interrogation of this database, results of which are delineated in the appended databases, revealed that immunodepleted murine MSCs (IDmMSCs) highly express transcripts encoding connective tissue proteins and factors modulating T-cell proliferation, inflammation, and bone turnover. Categorizing the transcriptome based on gene ontologies revealed the cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
53
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(59 citation statements)
references
References 81 publications
(80 reference statements)
5
53
0
1
Order By: Relevance
“…2,42,43 These analyses revealed that the MSC transcriptome reflected the developmental potential of the cells as depicted initially by the mesengenic process. 6 For example, both murine and human MSCs expressed a variety of developmentally regulated transcripts that play a role in the specification of mesoderm as well as transcripts characteristic of skeletal, adipose, muscle and endothelial tissue.…”
Section: The Msc Transcriptome Reflects the Functional Complexity Of mentioning
confidence: 90%
See 1 more Smart Citation
“…2,42,43 These analyses revealed that the MSC transcriptome reflected the developmental potential of the cells as depicted initially by the mesengenic process. 6 For example, both murine and human MSCs expressed a variety of developmentally regulated transcripts that play a role in the specification of mesoderm as well as transcripts characteristic of skeletal, adipose, muscle and endothelial tissue.…”
Section: The Msc Transcriptome Reflects the Functional Complexity Of mentioning
confidence: 90%
“…In the process of validating these findings it became evident that expression of many of these proteins was restricted to specific subpopulations. 43 Moreover, these expressed proteins were found to impart unique functional properties onto MSCs.…”
Section: The Msc Transcriptome Reflects the Functional Complexity Of mentioning
confidence: 99%
“…Networks have not been emphasized in previous transcriptomic studies on stem cells (4,21,27,33,35,38,40,42,43,46,49). The networks described in the present study may serve as a basis for future experiments.…”
Section: Discussionmentioning
confidence: 74%
“…A detailed description of the aforementioned SAGE databases has been published previously (22)(23)(24). Analysis of these databases revealed that the MSC transcriptome reflected both the developmental potential of MSCs as depicted by the mesengenic process and a capacity to regulate a broad array of biological processes important for bone and marrow function (Fig.…”
Section: Sage and The Msc Transcriptomementioning
confidence: 99%
“…In the latter case, MSCs were also found to express different classes of regulatory proteins important for angiogenesis, cell motility and communication, hematopoiesis, neural activities and immunity and defense. In the process of validating the SAGE data, it became evident that expression of different regulatory proteins was restricted to specific subpopulations of MSCs (24). Accordingly, we hypothesized that these subpopulations exhibit unique biological characteristics and as such contribute to the broad therapeutic efficacy of MSCs at the population level.…”
Section: Sage and The Msc Transcriptomementioning
confidence: 99%